Catalytic synthesis gas production in microchannel reactors - Şimşek, Eyüp. (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2012., 2012)
This dissertation presents syngas production from methane by steam and oxidative steam reforming in novel design wall-coated and packed microchannel reactors over δ-Al2O3 supported Ni and precious metal (Rh, Ru, Pd, Pt) based catalysts. Firstly, experimental design for determining performance test conditions was conducted to investigate the effects of reaction temperature, molar steam-to-carbon (S/C) ratio, particle size and addition of carbon dioxide to the feed over various catalysts including Ni/δ-Al2O3, Pt-Ni/δ-Al2O3, Pd/δ-Al2O3 Rh/δ-Al2O3 and Ru/δ-Al2O3 for MSR activity. The aim of second part of the study was to investigate and compare methane steam reforming (MSR) performances of precious metal and nickel catalysts, 2wt% Rh, 2wt% Ru, 2wt% Pd, and 10wt% Ni, for syngas production in two different microchannel reactor geometries, namely wall-coated and packed microchannels, operated at 873-1023 K and S/C ratios of 2.5-3.5, using a fixed inlet methane concentration and identical contact time of 7.22 mg.min.cm-3. In both cases, H2 and CO production rates over 2wt% Rh were the highest. It was found that H2/CO molar ratios in coated microchannel product streams are significantly lower than those in packed microchannels, 2wt% Rh is better in terms of CO selectivity while 10wt% Ni gives the highest H2 selectivity. Thirdly, oxidative steam reforming of methane (OSRM) performance of 0.2wt%Pt-2wt%Rh/δ-Al2O3 bimetallic catalyst was investigated in packed microchannel reactors, and compare its performance with coated microchannels, a parametric studyinvolving variations in reaction temperature, contact time, and steam-to-carbon and oxygen-to-carbon ratios was performed in the relatively lower contact time range of 0.41 to 0.71 mg·min·cm-3. Increase in all of the parameter values led to improvement in methane conversion, while CO selectivity increased only with temperature and contact time. In all cases, methane conversions in both microchannel configurations are found to be comparable with each other. CO selectivity, a critical parameter in syngas production, is found to be significantly higher in the coated microchannel configuration.
Keywords: Microreactors.; Microchemistry.; Catalysis.; Chemical reactors .